ECONOMIC ANALYSIS OF THE PROBLEM OF PRODUCTION IN CONSTRUCTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article theoretically and practically examines the impact of the production of construction products on the production of industrial products in the republic in 2000-2021. The role of the production of building materials in the production of industrial products is analyzed and a model of their interaction and connections between them is constructed.